2019
DOI: 10.24874/ijqr13.04-02
|View full text |Cite
|
Sign up to set email alerts
|

Towards a Characterization of BPM Tools’ Simulation Support: The Case of BPMN Process Models

Abstract: Due to the increasing acceptance of BPM (Business Process Management), nowadays BPM tools are extensively used in organizations. Core to BPM are the process modeling languages, of which BPMN is the one that has been receiving most attention these days. Once a business process is described using BPMN, one can use a process simulation approach in order to discover its optimized form. This paper analyzes the business process modeling and simulation areas, identifying the elements that must be present in the BPMN … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 3 publications
0
4
0
1
Order By: Relevance
“…Other components that are closely related to BPMN are processes, collaborations, and choreographies. Once a business process is described by using BPMN, a modeller can use a process simulation approach to discover its optimized form [8]. In course of time this approach attracted the attention of many reputable companies (Oracle, Intel, SAP etc.)…”
Section: Methods Used In the Researchmentioning
confidence: 99%
“…Other components that are closely related to BPMN are processes, collaborations, and choreographies. Once a business process is described by using BPMN, a modeller can use a process simulation approach to discover its optimized form [8]. In course of time this approach attracted the attention of many reputable companies (Oracle, Intel, SAP etc.)…”
Section: Methods Used In the Researchmentioning
confidence: 99%
“…The analysis of a few BPM tools [30] that forms the basis of this research has shown that, in addition to a minimal set of features that are required to do straightforward simulation work and are shared by all of them, there are considerably different simulation capabilities among tools. On the one hand, several BPM tools can already be used for significant simulation work, while on the other hand, there are still some that lack crucial simulation features.…”
Section: Bpmn and Simulationmentioning
confidence: 99%
“…According to [28], the axis of the BPM philosophy and the implementation of its principles is the satisfaction of customers' needs. BPM assists managers of SMEs in achieving business objectives [29]. One of the most important business objectives is customers satisfaction.…”
Section: Literature Reviewmentioning
confidence: 99%